Changes in the Correlation Between National and Territorial Identities in Contemporary Spain - A. V. Baranov (Ибероамериканские тетради, 2024)
Changes in the correlation between national and territorial identities in contemporary Spanish society have become a major factor behind the transformation of the political system and the rise of secessionist tendencies. Social constructivism argues that political actors purposefully determine the way identities are formed and how popular they are. Surveys and statements by political parties show that between 2011 and 2023 Spain saw exclusive national identity grow weaker to a certain extent and exclusive regional identity gain ground, while dual (composite) identity remained prevalent. A weaker national identity stems from the eroded credibility of national institutions, values and historical symbols of pride which, in turn, results from the opposite goals that identity policies of Catalonia and the Basque Country on the one hand and those of Spain’s government on the other pursue. Spain’s integration into the European Union has also taken a toll on national identity. A preference for national or regional identity closely correlates with respondents’ view of Spain’s ideal administrative division. Supporters of right-wing parties, middle-aged and elderly citizens, as well as monarchists express the strongest preference for national identity. Spaniards cite language as a crucial factor in shaping identity choice, with other factors being nationality, religion, gender, social class, autonomous community, ranked in order of importance. In 2023, 21 % of respondents all over Spain and over 43 % in Catalonia, the Basque Country and Navarre, where secession risk is high, perceive regional and local identities as rivals of Spanish national identity.